A barley PHD finger transcription factor that confers male sterility by affecting tapetal development - Fernandez Gomez, José Fernández; Wilson, Zoe A. (Wiley, 2014)
Controlling pollen development is of major commercial importance in generating hybrid crops and selective breeding, but characterized genes for male sterility in crops are rare, with no current examples in barley. However, translation of knowledge from model species is now providing opportunities to understand and manipulate such processes in economically important crops. We have used information from regulatory networks in Arabidopsis to identify and functionally characterize a barley PHD transcription factor MALE STERTILITY1 (MS1), which expresses in the anther tapetum and plays a critical role during pollen development. Comparative analysis of Arabidopsis, rice and Brachypodium genomes was used to identify conserved regions in MS1 for primer design to amplify the barley MS1 gene; RACE-PCR was subsequently used to generate the full-length sequence. This gene shows anther-specific tapetal expression, between late tetrad stage and early microspore release. HvMS1 silencing and overexpression in barley resulted in male sterility. Additionally, HvMS1 cDNA, controlled by the native Arabidopsis MS1 promoter, successfully complemented the homozygous ms1 Arabidopsis mutant. These results confirm the conservation of MS1 function in higher plants and in particular in temperate cereals. This has provided the first example of a characterized male sterility gene in barley, which presents a valuable tool for the future control of male fertility in barley for hybrid development.